2015
DOI: 10.1016/j.jom.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable evaluation and verification in supply chains: Aligning and leveraging accountability to stakeholders

Abstract: Please cite this article as: Gualandris, Jury, Klassen, Robert D., Vachon, Stephan, Kalchschmidt, Matteo, Sustainable evaluation and verification in supply chains: Aligning and leveraging accountability to stakeholders.Journal of Operations Management http://dx. ABSTRACTManagers are being challenged by multiple (and diverse) stakeholders, which have variety of expectations and informational needs about their firm's supply chains. Collectively, these expectations and needs form a multi-faceted view of stakehold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
293
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(296 citation statements)
references
References 82 publications
3
293
0
Order By: Relevance
“…This process represents a judges' validation and helped to adapt it to the context of the maquiladora industry [36,37].…”
Section: Phase 1 Sample Collectionmentioning
confidence: 99%
“…This process represents a judges' validation and helped to adapt it to the context of the maquiladora industry [36,37].…”
Section: Phase 1 Sample Collectionmentioning
confidence: 99%
“…This is supported by the study where presence of objectives related to customer service was extracted as one of items in factor loading 1 which a significant indicator for customer related performance measure. This outcome receives support from a perspective where organizations have been seen to set specific goals which are positively related to planning, quality and organizational performance [9]. A similar line of thinking was shared by Smith and Locke [10] who found that goals and task strategies were related to task performance and gave an assurance of future performance.…”
Section: Discussionmentioning
confidence: 62%
“…Such variation in goal alignment would suggest that the position and role of an organisation within the supply network influences its view of how it can effect change and thus which SDGs are most relevant. This view is supported by Schmidt et al [67] who note that, whilst stakeholders advocate "monolithic" outcomes across the supply chain, very different issues are salient for different companies, which therefore set different goals depending on their position within the supply network [68]. This highlights the difficulty of aligning goals and targets between different parts of the value network, even where strong relationships already exist.…”
Section: Observations and Comparisonsmentioning
confidence: 98%